Nutrients and not temperature are the key drivers for cyanobacterial biomass in the Americas - Bonilla, Sylvia; Aguilera, Anabella; Aubriot, Luis; Huszar, Vera; Almanza, Viviana; Haakonsson, Signe; Izaguirre, Irina; O'Farrell, Inés; Salazar, Anthony; Becker, Vanessa; Cremella, Bruno; Ferragut, Carla; et al. (Harmful algae, 2023)
•There were no clear latitudinal or climatic trends in cyanobacterial biomass.•Phosphorus was the main driver of cyanobacterial biomass throughout the Americas.•Nitrogen was most relevant in shallow lakes at high total phosphorus and high pH.•Temperature was not a significant factor in predicting cyanobacterial biomass.•Cyanobacteria management should focus on eutrophication and consider lake depth. Cyanobacterial blooms imperil the use of freshwater around the globe and present challenges for water management. Studies have suggested that blooms are trigged by high temperatures and nutrient concentrations. While the roles of nitrogen and phosphorus have long been debated, cyanobacterial dominance in phytoplankton has widely been associated with climate warming. However, studies at large geographical scales, covering diverse climate regions and lake depths, are still needed to clarify the drivers of cyanobacterial success. Here, we analyzed data from 464 lakes covering a 14,000 km north-south gradient in the Americas and three lake depth categories. We show that there were no clear trends in cyanobacterial biomass (as biovolume) along latitude or climate gradients, with the exception of lower biomass in polar climates. Phosphorus was the primary resource explaining cyanobacterial biomass in the Americas, while nitrogen was also significant but particularly relevant in very shallow lakes (< 3 m depth). Despite the assessed climatic gradient water temperature was only weakly related to cyanobacterial biomass, suggesting it is overemphasized in current discussions. Depth was critical for predicting cyanobacterial biomass, and shallow lakes proved more vulnerable to eutrophication. Among other variables analyzed, only pH was significantly related to cyanobacteria biomass, likely due to a biologically mediated positive feedback under high nutrient conditions. Solutions toward managing harmful cyanobacteria should thus consider lake morphometric characteristics and emphasize nutrient control, independently of temperature gradients, since local factors are more critical – and more amenable to controls – than global external forces.